Improving Implantation Rate in 2nd ICSI Cycle through Ovarian Stimulation with FSH and LH in GNRH Antagonist Regimen - Amanda Souza Setti; Daniela Paes de Almeida Ferreira Braga; Assumpto Iaconelli Júnior; Edson Borges Júnior (Revista Brasileira de Ginecologia e Obstetrícia, 2021)
Abstract Objective To investigate whether patients with a previous recombinant follicle stimulating hormone (rFSH)-stimulated cycle would have improved outcomes with rFSH + recombinant luteinizing hormone (rLH) stimulation in the following cycle. Methods For the present retrospective case-control study, 228 cycles performed in 114 patients undergoing intracytoplasmic sperm injection (ICSI) between 2015 and 2018 in an in vitro fertilization (IVF) center were evaluated. Controlled ovarian stimulation (COS) was achieved with rFSH (Gonal-f, Serono, Geneva, Switzerland) in the first ICSI cycle (rFSH group), and with rFSH and rLH (Pergoveris, Merck Serono S.p.A, Bari, Italy) in the second cycle (rFSH + rLH group). The ICSI outcomes were compared among the groups. Results Higher estradiol levels, oocyte yield, day-3 high-quality embryos rate and implantation rate, and a lower miscarriage rate were observed in the rFSH + rLH group compared with the rFSH group. In patients < 35 years old, the implantation rate was higher in the rFSH + rLH group compared with the rFSH group. In patients ≥ 35 years old, higher estradiol levels, oocyte yield, day-3 high-quality embryos rate, and implantation rate were observed in the rFSH + rLH group. In patients with ≤ 4 retrieved oocytes, oocyte yield, mature oocytes rate, normal cleavage speed, implantation rate, and miscarriage rate were improved in the rFSH + rLH group. In patients with ≥ 5 retrieved oocytes, higher estradiol levels, oocyte yield, and implantation rate were observed in the rFSH + rLH group. Conclusion Ovarian stimulation with luteinizing hormone (LH) supplementation results in higher implantation rates, independent of maternal age and response to COS when compared with previous cycles stimulated with rFSH only. Improvements were also observed for ICSI outcomes and miscarriage after stratification by age and retrieved oocytes.